Estudo do efeito sinérgico cavitação/erosão em revestimentos de carboneto de cromo e tungstênio depositados por aspersão térmica de alta velocidade - Bertuol, Kauê (2020)
Cavitation wear, solid particle erosion and synergistic cavitation/erosion are common problems in hydroelectric plants, as they cause hydraulic component wear and generate high costs in the production of electricity. One way to improve the surface resistance of these components is by depositing high wear resistant materials, such as carbide coatings. Thus, this work proposes the deposition of Cr3C2 25NiCr and WC 10Co4Cr by HVOF, aiming to study the behaviour of these coatings in cavitation, erosion and synergistic wear resistance. After the spraying process, the porosity, present phases, hardness and fracture toughness of the coatings were analysed. The mass loss and wear mechanisms of these coatings were evaluated in tests such as: pure distilled water cavitation, cavitation on fluid with sand microparticles and slurry jet erosion at different impact angles. The porosity found in the Cr3C2 25NiCr coating was smaller than the WC 10Co4Cr. The higher fracture toughness of Cr3C2 25NiCr was attributed to the high concentration of the NiCr metal matrix and the low porosity of the coating. In the cavitation tests, the wear rate of Cr3C2 25NiCr coating was lower than WC 10Co4Cr, and both coatings higher than CA6NM. Factors such as porosity and fracture toughness were important in the cavitation resistance of the materials. In the sand cavitation/erosion synergistic wear test, a clear increase in the wear rate of both coatings was noted. Cr3C2 25NiCr stood out as the most sensitive coating to the erosive effect of microparticles during the cavitation process, increasing the wear rate by approximately 260% after adding sand. Cavitation wear started preferentially in the pores and pre-existing surface defects, but the formation of cracks, detachment and cracking of carbides may have intensified with the presence of sand impacting the surface of the coatings. In slutty jet erosion test, WC 10Co4Cr showed greater wear resistance than Cr3C2 25NiCr, and both were higher than CA6NM steel. With an angle of impact of 90°, coatings showed microploughing of the metal matrix and carbide detachment, while Cr3C2 25NiCr showed more homogeneous wear of matrix and carbides, in WC 10Co4Cr carbide cracking was observed. CA6NM presented basically plastic deformation of the microploughing type. The ductile or brittle behaviour of materials in slurry jet erosion test under different impact angles was decisive in the intensity and mechanism of wear. At 30° both coatings showed a decrease in the erosive wear rate, while CA6NM increased with the decrease of the impact angle.